Mapping the Methanol‐to‐Gasoline Process Over Zeolite Beta - Ye, Yiru; Abou‐Hamad, Edy; Gong, Xuan; Shoinkhorova, Tuiana B.; Dokania, Abhay; Gascon, Jorge; Chowdhury, Abhishek Dutta (Angewandte Chemie International Edition, 2023)
Decarbonizing the transportation sector is among the biggest challenges in the fight against climate change. CO2‐neutral fuels, such as those obtained from renewable methanol, have the potential to account for a large share of the solution, since these could be directly compatible with existing power trains. Although discovered in 1977, the zeolite‐catalyzed methanol‐to‐gasoline (MTG) process has hardly reached industrial maturity, among other reasons, because maximizing the production of gasoline range hydrocarbons from methanol has proved complicated. In this work, we apply multimodal operando UV/Vis diffuse reflectance spectroscopy coupled with an online mass spectrometer and “mobility‐dependent” solid‐state NMR spectroscopy to better understand the reaction mechanism over zeolites H‐Beta and Zn‐Beta. Significantly, the influential co‐catalytic role of oxymethylene species is linked to gasoline formation, which impacts the MTG process more than carbonylated species. A multimodal and complementary spectroscopic strategy (involving operando UV/Visible spectroscopy coupled to online mass spectrometry and solid‐state NMR spectroscopy) delivers a mechanistic blueprint of the zeolite‐catalyzed methanol‐to‐gasoline process by elucidating the impact of carbonylated and oxymethylene species.